Long‐term outcomes after endoscopic submucosal dissection for differentiated‐type early gastric cancer that fulfilled expanded indication criteria: A prospective cohort study. Issue 3 (6th August 2020) - Shichijo, Satoki; Uedo, Noriya; Kanesaka, Takashi; Ohta, Takashi; Nakagawa, Kentaro; Shimamoto, Yusaku; Ohmori, Masayasu; Arao, Masamichi; Iwatsubo, Taro; Suzuki, Sho; Matsuno, Kenshi; Iwagami, Hiroyoshi; et al.
Abstract: Background and Aim: Endoscopic resection for early gastric cancer (EGC) is widely performed. However, there is still a paucity of strong evidence regarding long‐term outcomes after endoscopic submucosal dissection (ESD) for the expanded indication criteria of the Japanese guidelines (ver. 2010). Methods: Endoscopic submucosal dissection was performed in patients with EGC that met the expanded indication criteria: (i) cT1a, differentiated‐type EGC of 2 to 5 cm, ulcer negative or (ii) cT1a, differentiated‐type EGC of ≤3 cm, ulcer positive. Patients whose pathological examination fulfilled the curative resection criteria were then enrolled in this cohort study: negative vertical margin, negative lymphovascular invasion, and (i) pT1a, differentiated‐type, and ulcer negative; (ii) pT1a, differentiated‐type, ≤3 cm, and ulcer positive; or (iii) pT1b1 (<500‐μm submucosal invasion), differentiated‐type, and ≤3 cm. Patients with only a positive horizontal margin as a noncurative factor were included for follow‐up. Results: From September 2003 to February 2012, a total of 356 patients underwent ESD, and 214 were enrolled in the survival analysis. One hundred twenty patients (56%) had >2 cm in diameter and ulcer‐negative lesions, and 94 (44%) had ≤3 cm and ulcer‐positive lesions. The vital status at 5 years after ESD was confirmed in all (100%) patients. No local or metastatic recurrence was detected; however, 26 metachronous gastric cancers developed, and 1 patient died of metachronous gastric cancer. The 5‐year disease‐specific and overall survival rates were 99.5% (95% confidence interval [CI], 97.2%–100%) and 93.9% (95% CI, 89.8%–96.4%), respectively. Conclusion: ESD for EGC that fulfills the expanded criteria is feasible and shows favorable long‐term outcomes.